2016
DOI: 10.1121/1.4972336
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm mitigation by drug (gentamicin)-loaded liposomes promoted by pulsed ultrasound

Abstract: The gentamicin-loaded nano-sized liposomes are shown to penetrate into alginate-based Ralstonia insidiosa bacterial biofilms by acoustic streaming generated by moderate pulsed ultrasound (frequency = 2.25 MHz, 10% duty cycle and spatially and temporally averaged intensity, I ≈ 4.4 W/cm). The liposomes are then burst by the scanned relatively high intensity ultrasound (frequency = 1.1 MHz, 10% duty cycle, the spatially and temporally averaged intensity I ≈ 90 W/cm) in situ, and the gentamicin solution is releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This inhibition could be maintained during 6 h, while no inhibition was observed in the case of free nisin at this time. In another work, Ma and Wu (2016) prepared gentamicinloaded liposomes to penetrate into alginate-based Ralstonia insidiosa biofilm in the presence of acoustic streaming created by pulsed ultrasound. The ultrasound pushed the liposomes into alginate-based biofilm.…”
Section: Antibacterial Nanoparticles Against Biofilm Bacteriamentioning
confidence: 99%
“…This inhibition could be maintained during 6 h, while no inhibition was observed in the case of free nisin at this time. In another work, Ma and Wu (2016) prepared gentamicinloaded liposomes to penetrate into alginate-based Ralstonia insidiosa biofilm in the presence of acoustic streaming created by pulsed ultrasound. The ultrasound pushed the liposomes into alginate-based biofilm.…”
Section: Antibacterial Nanoparticles Against Biofilm Bacteriamentioning
confidence: 99%
“…Bacteria were efficiently eradicated using gentamicin containing liposomes following ultrasonic treatment. [74,75] The authors also noted that non-focused US increases liposome penetration into the biofilm, [74] and that focused US efficiently bursts the liposomes, thus releasing the contained drugs. [75]…”
Section: Liposomesmentioning
confidence: 99%
“…In another work [29], the authors showed that the focused US and gentamicin-encapsulated liposomes reduced the number of viable bacteria in alginate-based Ralstonia insidiosa biofilms by approximately 72%, compared to US alone, gentamicin in solution alone (no liposomes) and gentamicin in solution with high-intensity focused US. These data show that high-intensity focused US in combination with an antibiotic strategy can kill bacteria within synthetic alginate biofilms, while non-focused US was able to increase the attachment of liposomes to the biofilm, as demonstrated by the same authors [30].…”
Section: Exogenous Stimuli-responsive Antibiotic Drug-delivery Sysmentioning
confidence: 99%